The phenomenon of Haraba in the Islamic West A socio-historical study (6-8 A.H./12-14 A.D.) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Today's historical writing is characterized by its openness to social topics that were until recently classified as forgotten topics. Hence, this attention to the topic of “Haraba”‌ came to unveil a negative social phenomenon that society suffered in the Islamic West in the period between the two centuries (6-8 AH/12-14 AD), as it is one of the hidden investigations in the field of historical writing.This research studies this social scourge, in order to understand and analyze this aggressive behavioral pattern, in the light of the extrapolation of various historical texts, in order to arrive at the causes of the phenomenon of enmity, which varies between pressing economic reasons, difficult living conditions, or behavioral deviations and humiliation of transgression as a way of living, regardless. Regardless of the circumstances, the research deals with the results of this phenomenon on the economic activities of agriculture and trade, and its psychological impact on the population, travelers, and merchants of fear, anxiety and anticipation, in addition to the measures taken to reduce enmity, whether at the official level represented by rulers and jurists, or at the popular level represented The general public, who in turn participated in precautionary and preventive measures against this phenomenon.